Satellitome of the Red Palm Weevil, Rhynchophorus ferrugineus (Coleoptera: Curculionidae), the Most Diverse Among Insects - Montiel, Eugenia E.; Mora, Pablo; Rico-Porras, José M.; Palomeque, Teresa; Lorite, Pedro (Frontiers in Ecology and Evolution, 2022)
The red palm weevil, Rhynchophorus ferrugineus, is the most harmful species among those pests affecting palm trees. Its impact causes important economic losses around the World. Nevertheless, the genetic information of Rh. ferrugineus is very scarce. Last year, the first genome assembly was published including a rough description of its repeatome. However, no information has been added about one of the main components of repeated DNA, the satellite DNA. Herein, we presented the characterization of the satellitome of this important species that includes 112 satellite DNA families, the largest number in an insect genome. These satellite DNA families made up around 25% of the genome while the most abundant family, RferSat01-169, alone represented 20.4%. Chromosomal location of most abundant satellite DNA families performed by fluorescence in situ hybridization showed that all of them are dispersed in the euchromatin on all chromosomes but some of them are also specifically accumulated either on the pericentromeric heterochromatic regions of all chromosomes or on specific chromosomes. Finally, the transcription of satellitome families was analyzed through Rh. ferrugineus development. It was found that 55 out of 112 satellite DNA families showed transcription, some families seemed to be transcribed across all stages while a few appeared to be stage-specific, indicating a possible role of those satellite DNA sequences in the development of this species.